Regional Educational Policy Analysis: Rochester, Omaha, and Minneapolis' Inter-District Arrangements. (July 2015) - Finnigan, Kara S.; Holme, Jennifer Jellison; Orfield, Myron; Luce, Tom; Diem, Sarah; Mattheis, Allison; Hylton, Nadine D.
Although regional equity scholars have demonstrated how cross-jurisdictional collaboration on transportation, housing, and employment can promote opportunity for low-income families, few have paid serious attention to the potential of regional educational policy to improve opportunity for children. This study seeks to address this gap by examining inter-district "collaboratives" or cooperative agreements between school districts within a metropolitan area. These collaborative arrangements address two inter-related demographic shifts: the rising level of segregation in public schools and the shift from within district segregation to between-district segregation. This article examines three regional collaboratives (Rochester, NY, Omaha, NE, and Minneapolis, MN) that involve varying degrees of cooperation, funding, and legal force. Drawing on 60 in-depth interviews across the three sites, this analysis considers how each program's design features interact with local political dynamics to shape the degree to which these collaboratives are able to achieve policy goals.